(untitled) (European Journal of Pure and Applied Mathematics, 2023)
This paper is concerned with the concepts of s(Λ, b)-open sets, p(Λ, b)-open sets, α(Λ, b)-open sets, β(Λ, b)-open sets and b(Λ, b) open sets. Some properties of s(Λ, b)-open sets, p(Λ, b)-open sets, α(Λ, b)-open sets, β(Λ, b)-open sets and b(Λ, b)-open sets are investigated. Moreover, several characterizations of weakly (Λ, b)-continuous functions are established.